2003
DOI: 10.1182/blood-2002-09-2708
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1 and GATA-1 coexpression and cooperation in megakaryocytic differentiation

Abstract: Megakaryocytic and erythroid lineages derive from a common bipotential progenitor and share many transcription factors, most prominently factors of the GATA zinc-finger family. Little is known about transcription factors unique to the megakaryocytic lineage that might program divergence from the erythroid pathway. To identify such factors, we used the K562 system in which megakaryocyte lineage commitment is dependent on sustained extracellular regulatory kinase (ERK) activation and is inhibited by stromal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
290
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(305 citation statements)
references
References 62 publications
11
290
1
2
Order By: Relevance
“…Taken together, our current findings suggest that interactions between currently unidentified cofactors and the GATA1 N-terminus facilitate chromatin occupancy specifically at erythroid genes. RUNX1 and the retinoblastoma protein (Rb) bind the GATA1 N-terminus (55,56). However, loss of RUNX1 in hematopoietic progenitors impairs megakaryopoiesis, but not erythropoiesis (reviewed in ref.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, our current findings suggest that interactions between currently unidentified cofactors and the GATA1 N-terminus facilitate chromatin occupancy specifically at erythroid genes. RUNX1 and the retinoblastoma protein (Rb) bind the GATA1 N-terminus (55,56). However, loss of RUNX1 in hematopoietic progenitors impairs megakaryopoiesis, but not erythropoiesis (reviewed in ref.…”
Section: Methodsmentioning
confidence: 99%
“…24 In addition to its gene dosage effects, AML1 coexpresses and cooperates with GATA1 in megakaryocytic differentiation. 25 ETS2 and ERG (ETS transcription factor family members) have been shown to be overexpressed in adult myeloid leukemia cases with complex acquired karyotypes involving chromosome 21. 26 This suggests that these two genes may also play important roles in leukemogenesis in individuals with DS, since both genes are located on chromosome 21q22 within the minimal DS region.…”
Section: Introductionmentioning
confidence: 99%
“…Inherited mutations in either GATA-1 or Runx1 are associated with congenital thromobocytopenia (15)(16)(17)(18)(19)(20)(21). Furthermore, in vitro studies suggest that GATA-1:Runx1 complex formation regulates megakaryocyte differentiation (22). Studies in Drosophila have identified hematopoietic functions for homologues of GATA, FOG, and Runx class genes (23)(24)(25)(26).…”
mentioning
confidence: 99%